2006
DOI: 10.1074/jbc.m601108200
|View full text |Cite
|
Sign up to set email alerts
|

The Electron Transfer Complex between Cytochrome c552 and the CuA Domain of the Thermus thermophilus ba3 Oxidase

Abstract: The structural analysis of the redox complex between the soluble cytochrome c 552 and the membrane-integral cytochrome ba 3 oxidase of Thermus thermophilus is complicated by the transient nature of this protein-protein interaction. Using NMR-based chemical shift perturbation mapping, however, we identified the contact regions between cytochrome c 552 and the Cu A domain, the fully functional water-soluble fragment of subunit II of the ba 3 oxidase. First we determined the complete backbone resonance assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 48 publications
6
55
1
Order By: Relevance
“…Previous pathways calculations considering only the σ u * ground state weighted by metalligand covalencies suggested that the Cys ligands act as the electron access point (26). However, our pathways analysis in the ET complex between cytochrome c 552 (Cyt c 552 ) and the Cu A domain of T. thermophilus (13) reveals that the axial Met160 ligand provides the favored electron entry point to the Cu A site (SI Appendix, Tables S6 and S7). Even though the metal-ligand covalency is very low for the axial Cu-S Met bond in the σ u * ground state (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous pathways calculations considering only the σ u * ground state weighted by metalligand covalencies suggested that the Cys ligands act as the electron access point (26). However, our pathways analysis in the ET complex between cytochrome c 552 (Cyt c 552 ) and the Cu A domain of T. thermophilus (13) reveals that the axial Met160 ligand provides the favored electron entry point to the Cu A site (SI Appendix, Tables S6 and S7). Even though the metal-ligand covalency is very low for the axial Cu-S Met bond in the σ u * ground state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, transient binding of redox protein partners is known to modify the reduction potential of donor and acceptor sites (28) and to induce geometrical distortions of copper redox centers (29,30). In fact, the study of the Cyt 552 -Cu A complex reveals subtle structural perturbations at the Cu A site in a redox state-dependent fashion (13). In addition, the prediction that moderate electric fields alter the barrier for σ u *-π u interchange suggests that the local membrane potential could exert regulation on the electroprotonic energy transduction, as previously proposed based on different evidence (31,32).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron transfer in T. thermophilus between complex III and the terminal oxidases had previously been analyzed by a variety of structural and kinetic approaches (5,7,9,10,14,22). Using soluble fragments of redox protein complexes to determine ET interactions has proven a successful approach (5, 6, 9, 23 -26): it offers the advantages of a simplified experimental handling, as no detergents are required, and avoids kinetic interference from subsequent internal ET or energy transducing steps, allowing the following of only the single ET reaction of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Electron transfer (ET) between the bc-complex and the terminal oxidases via cytochrome c 552 has been studied by presteady state (5,6,9) and steady-state (3, 10, 13) kinetics as well as NMR and computational approaches (14), revealing fast and efficient ET reactions (bimolecular rate constants of ca.…”
Section: Introductionmentioning
confidence: 99%